Molecular motion of donor–acceptor catenanes in water1. Issue 10 (14th March 2015) - Cougnon, Fabien B. L.; Ponnuswamy, Nandhini; Pantoş, G. Dan; Sanders, Jeremy K. M.
<x xml:space="preserve">Abstract</x> In this article, we use 1H NMR spectroscopy to study the spontaneous molecular motion of donor–acceptor [2]catenanes in water.